IN-SILICO ASSESSMENT OF COMMON ?-GLOBIN GENE MUTATIONS FOUND IN KHYBER PAKHTUNKHWA, PAKISTAN - Jalil, Tehmina; Rashid, Ibrahim; Shah, Inayat; Khan, Ilyas; Yousafzai, Yasar Mehmood (Pakistan Journal of Physiology, 2018)
Background: ?-thalassaemia manifests a spectrum of clinical phenotypes, ranging from mild subclinical disease to severe transfusion-dependent anaemia. This remarkable diversity of disease patterns is not completely explained, but various disease modifying factors have been identified and categorized in to primary, secondary and tertiary modifiers. Nearly 300 mutations in ?-globin genes (HBB) have been reported so far. In our previous study we identified six mutations; (Cd 5 (-CT), FR 8-9(+G), FR 16(-C), FR 41-42(-TTCT), Cd 30(G>A) and Cd 15(G>A) to be the most frequent ones in Khyber Pakhtunkhwa province of Pakistan. It is aimed to observe if bioinformatics tools could be used to construct the structure of globin chains carrying these six common mutations. Methodology: Using a computational approach, the sequences of mutated HBB were hypothetically constructed, protein structures were formulated and analysed for homology, and post-translational modifications. In mutations where protein structure formation is halted in vivo, stop codons from the DNA sequence of each of the mutational variant were exclude to allow further analysis. Results: These mutants exhibited variable post-translational modification pattern with little effect on overall structure. Mutations at critical sequences in HBB that do not allow further translation of HBB in vivo and did not stop computer modelling from developing protein structure in-silico. Conclusion: Computational analysis for constructing mutant proteins does not take into account some of the critical checkpoints present in the cell. Studies using computational analysis should be followed by rigorous in vivo validation. Pak J Physiol 2018;14(3):68–73